Population research centre university of groningen: The first child the transition to motherhood in Japan and the Netherlands. - Matsuo, Hodeko (2001)
ABSTRACT: Many women In Japan and The Netherlands are either not giving birth or postponing their first birth. Empirical evidence show that approximately 20% of women are childless in both countries and mean age of first birth is 27.9 years for Japan and 28.6 years in The Netherlands. The research analyses the occurrence and timing of first birth in both countries and tries to situate these life events within the broader framework of the Second Demographic Transition. The proposed theoretical framework is based on process context approach and uses Social Theory, value -expectancy model, in particular, Theory of Planned Behaviour. A life course perspective is adopted in which cognitive variables related to value orientation and first birth (behavioural outcome) becomes time and context specific. In this study, we present the theoretical framework to study the association between value orientation and occurrence and timing of first birth. We also examine the empirical evidence and focus on variables, such as, value orientation, on one hand, first birth on the other hand. The Netherlands Fertility Survey of 1993 and Japanese National Fertility Survey of 1992 are examined for this purpose. The preliminary results shows that no significant differences in socio-economic characteristics exist between women who do not have a child and those postponing their first births. The findings also show that value orientation changes over life course, and furthermore, its characteristics and occurrence and timing those women in Japan and The Netherlands experience changes in value orientation over various birth cohorts and these changes can influence the occurrence and timing of first birth. Keywords: Value-expectancy model, Occurrence and timing of first birth, childlessness, Postponement effects, value orientation